H. Hart’s Criticism of H. Kelsen’s Doctrine of Unity, Consistency and Autonomy of Law - Sergei N. Kasatkin (RUDN Journal of Law, 2025)
The author examines the debate surrounding the understanding and possibility of normative conflicts within legal systems, focusing on theories of 20th-century key positivists, Kelsen and Hart. The primary aim is to reconstruct and evaluate Hart’s critique of Kelsen’s concept of the impossibility of norm conflicts, which is central to Kelsen’s doctrine of the unity of the system of law (both international and municipal) and its relationship with morality. The paper’s relevance stems from the controversial comparative assessment of Kelsen and Hart’s positions on norm conflicts, the relatively unexplored nature of Hart’s doctrine on this issue, and the need to clarify the foundations for conceptualizing norm conflicts at the intersection of foreign and domestic legal experiences. The main sources are Kelsen’s classical works and Hart’s 1960s essays analyzing them, studied using ideological-historical and rational reconstruction, exegesis, and philosophical analysis of language. The article analyzes the jurists’ general approaches, their accounts of the unity, consistency, and autonomy of law, and evaluates their methodological and practical potential. The main conclusion is that the possibility of norm conflicts in law depends on the “interpretative attitude” and the language of reasoning accepted within a community, and that theoretical statements about the possibility of such conflicts are contingent upon the chosen methodology.